Physico-chemical characterization of slag occurrences at Tilva Njagra locality, Bor region, Eastern Serbia - Živković Dragana; Štrbac Nada; Cocić M.; Andrić V.; Šteharnik M.; Budić S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Physico-chemical characterization of slag occurrences at Tilva Njagra locality (Bor region, Eastern Serbia) was done and the results of the research activities are presented in this paper. The samples were investigated using chemical analysis, XRD, DTA and EDXRF.